PENGARUH FAKTOR MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN DENGAN PANDEMI COVID-19 SEBAGAI VARIABEL MODERATING PADA BURSA EFEK INDONESIA - Khoirotul Kiptiyah; Nur Diana; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aimed to analyze and test the effect of Inflation, Interest Rates, and Exchange Rates on the Composite Stock Price Index with the covid-19 pandemic as a moderating variable. This study uses a quantitative correlational approach. The location of this research was conducted on the Indonesia Stock Exchange. This research will be conducted in February 2021 until it is completed. The population in this study is the Indonesia Stock Exchange for the period 2018 to 2020. Sampling was carried out based on the purposive sampling method, with predetermined criteria, so 104 samples were obtained. The results of the study state that partially, Inflation, Interest Rates, Exchange Rates, and the Covid-19 Pandemic have a negative effect on the Composite Stock Price Index, and partially Inflation, Interest Rates and Exchange Rates have a negative effect on the Composite Stock Price Index with the covid-19 pandemic as a moderating variable.Keywords: Inflation, Interest Rates, Exchange Rates, Covid-19 Pandemic, and Composite Stock Price Index